Mendelian randomization analyses reveal novel drug targets for anorexia nervosa - Yang, Jian; Fan, Yajuan; Yan, Bin; Zhao, Binbin; Qian, Li; Gao, Fengjie; Ma, Qingyan; Yang, Lihong; Wang, Wei; Bai, Ling; Zhu, Feng; Ma, Xiancang (Progress in neuro-psychopharmacology & biological psychiatry, 2022)
Among all psychiatric disorders, anorexia nervosa (AN) has the highest mortality rate. However, there is still no pharmacological therapy for AN. The human plasma proteome may be a great cornerstone for the development of new drugs against AN. Here we performed a Mendelian randomization (MR) analysis to identify causal risk proteins for AN. Exposure data were extracted from a large genome-wide association study (GWAS) of 2994 plasma proteins in 3301 subjects of European descent, while outcome data were obtained from another GWAS of AN (16,992 cases and 55,525 controls of European descent). MR analyses were performed using the inverse-variance weighted (IVW) method and other sensitivity analysis methods. Using single nucleotide polymorphisms as instruments, this study suggested that high TXNDC12 levels were associated with a higher risk of AN (IVW Odd's ratio [OR]: 1.12; 95% confidence interval [CI]: 1.08–1.16; P = 2.35 × 10−10), while another protein ADH1B showed the opposite effect (IVW OR: 0.89; 95% CI: 0.85–0.93; P = 2.99 × 10−7). The causal associations were robust in multivariable models, genome-wide significant models, and with additional MR methods. No pleiotropy was observed. Our findings suggest that TXNDC12 was associated with a high risk of AN, while AHD1B was associated with a low risk of AN. They might both have implications in AN by regulating the brain dopamine reward system. In combination with existing knowledge on AN, these proteins may be novel drug targets for AN treatment. [Display omitted] •Increase in level of TXDNC12 in human serum is associated with higher risk of AN.•Increase in level of ADH1B in human serum is associated with lower risk of AN.•Both TXDNC12 and ADH1B might play roles in AN by regulating the dopamine reward system.